Pengaruh Kualitas Produk dan Pengalaman Pelanggan terhadap Minat Pembelian Kembali Melalui Kepuasan Konsumen pada Produk Fashion di Marketplace Tiktok Shop - I Gede Angga Jimawan; Luh Putu Mahyuni (Jurnal Manajemen, Bisnis dan Kewirausahaan, 2026)
This study aims to analyze the influence of product quality and customer experience on repurchase intention, with customer satisfaction as a mediating variable, in the context of fashion products on TikTok Shop. The research addresses gaps in prior studies related to consumer behavior on rapidly growing social commerce platforms, while also providing strategic recommendations for digital marketing practitioners. A quantitative online survey was conducted using purposive sampling targeting consumers in Bali who had previously purchased fashion products from TikTok Shop. Primary data were collected through a Likert-scale questionnaire and analyzed using PLS-SEM, including assessments of validity and reliability through the outer model and structural relationship testing via the inner model. The results indicate that both product quality and customer experience have a positive and significant effect on customer satisfaction. Furthermore, customer satisfaction significantly increases repurchase intention. The indirect effect analysis confirms that satisfaction acts as a mediator between product quality and customer experience toward repurchase intention. A key finding of this research is that product quality serves as the most dominant factor influencing satisfaction and encouraging repeat purchases compared to customer experience. The implications highlight the importance of maintaining consistent product quality and optimizing interactive shopping experiences on live-commerce platforms to enhance customer loyalty on TikTok Shop.